GALS for gender-transformative research (GALS4GTR): A tool in the CGIAR Gender Transformative Research Methodologies (GTRM) toolkit - Enokenwa Baa, Ojongetakah; Liani, Millicent L; Mapedza, Everisto; Tristan, Maria Claudia; Yap, Tina; Osei Amponsah, Charity (2025)
Tool 2 in the Gender Transformative Research Methodologies Toolkit. Through structured steps, it addresses inequalities, shifts norms and attitudes, and supports communities in anticipating challenges and building networks. The information generated helps research practitioners to diagnose gender issues, co-design gender-transformative solutions, and support the management of unintended impacts through tailored monitoring and evaluation processes. Main focus on households and communities.